Internal auditors role indicators and their support of good governance - Sri Rahayu (Taylor & Francis Group, 2020)
The study aimed to develop indicators to measure the implementation of a new model for internal auditors in government organizations and their support of good public governance. Data was collected through a survey, with questionnaires, and interviews with key informants. Respondents were internal auditors from various government organizations. Data were analyzed using both quantitative and qualitative analysis. Internal auditors can carry out roles under a new model if they receive support in the form of leadership commitment. Currently, the dominant role of government internal auditors is as a watchdog. Roles as consultants and catalysts have begun to be implemented, although they are not yet optimal. The control variable provided the highest support for good public governance, while the audit knowledge variable provided the lowest support. The government needs to focus on increasing the quantity and capability of internal auditors through training, outreach, and technical guidance.